The development of drowning prevention strategies model in Malaysia: need survey analysis / Muhammad Wafi A. Rahman ... [et al.]. - A. Rahman, Muhammad Wafi; Mohd Yasim, Mazuki; Ibrahim, Azli; Md Taff, Md Amin; Johanis, Nik Jazwiri; Safie, Mohd Shariman (2024)
Drowning remains a significant public health concern in Malaysia, particularly among children. Despite ongoing efforts to mitigate this risk, there is a pressing need for a comprehensive drowning prevention model tailored to the Malaysian context. This study aims to develop a drowning prevention strategies model through an extensive need survey analysis among parents, educators, and community leaders. Therefore, the main purpose of this study was to know the scenario and the need for analysis of the drowning prevention model from the expert point of view. The study is based on the Develop and Design Research (DDR; Saedah, Muhammad & Rozaini, 2020). IBM Statistics (SPSS) is utilized as the main statistical analysis software. A total of 187 respondents (N = 187) among units of Pasukan Penyelamat di Air (PPDA) under Jabatan Bomba dan Penyelamat Malaysia (JPBM) have purposively been selected. Based on the analyses, over 90% of agree was achieved for all statements in the survey. These findings provided a platform and systematic scholarly work on strategies for drowning prevention model development.